Potent social synchronization can override photic entrainment of circadian rhythms - Fuchikawa, Taro (Nat Commun, 2016)
Circadian rhythms in behaviour and physiology are important for animal health and survival. Studies with individually isolated animals in the laboratory have consistently emphasized the dominant role of light for the entrainment of circadian rhythms to relevant environmental cycles. Although in nature interactions with conspecifics are functionally significant, social signals are typically not considered important time-givers for the animal circadian clock. Our results challenge this view. By studying honeybees in an ecologically relevant context and using a massive data set, we demonstrate that social entrainment can be potent, may act without direct contact with other individuals and does not rely on gating the exposure to light. We show for the first time that social time cues stably entrain the clock, even in animals experiencing conflicting photic and social environmental cycles. These findings add to the growing appreciation for the importance of studying circadian rhythms in ecologically relevant contexts.